Oil Spills, Climate Change, Pollution and Land Decay: Media Framing of Environmental Issues in the Iraqi Media - Dhaher, Cjyar Nazar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
Iraq is a significant country in the Middle East and significant natural resources in Iraq include natural gas and petroleum. Refining Iraqi oil causes serious environmental issues such as oil spillage, air, water, and land pollution and all of these problems contribute to climate change. Several studies have associated air, water, and land pollution with wars and oil spillage which is a form of pollution that can be viewed from the perspective of intentional and unintentional acts. In many cases, the way the media presents their understanding of the issue instead of how the audiences understand it and should understand it. As a result of the limited comprehensive study dissecting the diverse media frame of oil spills, pollution, and land decay in Iraq, this study is necessary to fill this research vacuum by evaluating the media framing of oil spills, pollution, and land decay in Iraq. Quantitative content analysis in combination with frame theory and agenda-setting theory was applied to examine the reflection of newspapers in media framing of oil spills, climate change, pollution, and land destruction in Iraq. The study concludes that news on environmental issues has been well discussed in the Iraqi media. The reflexivity shown in newspaper coverage suggests that Iraqi investigative journalism may play an advocacy role in portraying environmental problems in a reactive manner that confronts and criticizes Iraq's official goals. The study recommends that since newspapers are a widely used news medium in Iraq, news can now be sent to individual residents via social media 24 hours a day.

ÖZ: Irak, Orta Doğu'da önemli bir ülkedir ve Irak'taki önemli doğal kaynaklar arasında doğal gaz ve petrol bulunmaktadır. Irak petrolünün rafine edilmesi, petrol sızıntısı, hava, su ve toprak kirliliği gibi ciddi çevre sorunlarına yol açmakta ve tüm bu sorunlar iklim değişikliğine katkıda bulunmaktadır. Çeşitli araştırmalar hava, su ve toprak kirliliğini savaşlar ve kasıtlı ve kasıtsız eylemler açısından bakılabilecek bir kirlilik türü olan petrol döküntüsü ile ilişkilendirmiştir. Çoğu durumda, izleyicilerin konuyu nasıl anladıkları ve anlamaları gerektiği yerine, medyanın konuyu nasıl anladıklarını sunma şekli. Irak'taki petrol sızıntıları, kirlilik ve arazi bozulmasına ilişkin çeşitli medya çerçevesini inceleyen sınırlı kapsamlı çalışmanın bir sonucu olarak, bu çalışma, Irak'taki petrol sızıntıları, kirlilik ve arazi bozulmasına ilişkin medya çerçevesini değerlendirerek bu araştırma boşluğunu doldurmak için gereklidir. Gazetelerin Irak'taki petrol sızıntıları, iklim değişikliği, kirlilik ve arazi tahribatının medya çerçevelemesindeki yansımasını incelemek için çerçeve teorisi ve gündem belirleme teorisi ile birlikte nicel içerik analizi uygulandı. Çalışma, Irak medyasında çevre konularıyla ilgili haberlerin iyi tartışıldığı sonucuna varıyor. Gazete haberlerinde gösterilen yansıma, Irak araştırmacı gazeteciliğinin, Irak'ın resmi hedefleriyle yüzleşen ve onları eleştiren tepkisel bir biçimde çevre sorunlarını tasvir etmede savunuculuk rolü oynayabileceğini öne sürüyor. Çalışma, gazetelerin Irak'ta yaygın olarak kullanılan bir haber aracı olması nedeniyle, artık sosyal medya aracılığıyla 24 saat haberlerin bireysel olarak bölge sakinlerine gönderilebileceğini önermektedir.
Doctor of Philosophy in Communication and Media Studies. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Communication And Media Studies, 2023. Supervisor: Prof. Dr. Agah Gümüş.
Keywords: Communication and Media Studies Department; Social Media in Iraq--Social Networking Sites--Environmental Issues--Iraq; Environmental Aspects--Media--Iraq; Mass media and the environment; Media framing; oil spillage; Iraq; pollution; land decay